Flashcards as A Media in Teaching English Vocabulary - La Aba (Al-Lisan: Jurnal Bahasa, 2019)
This article aims to observe the using of flashcard as a media in teaching English vocabulary. The importance of language element is vocabulary because it is the vital organ of language. Teaching language needs media to deliver material to motivate the students and to put material easy to be understood. Therefore, this article examines two questions, namely how flashcard was used as media in teaching English vocabulary and is flashcards media effective in teaching English vocabulary. Classroom Action Research was used as a research method in this research. The result showed that the flashcard was prepared by teacher according to his/her creativity, such as the size and the content of words on the flashcards. The teacher used models of teaching vocabulary using flashcards, namely rhyme and lines flashcards, vocabulary introduction, find the pictures, story cards, categorizing vocabulary, and flashcard memory game. All the models have their steps. The result of research also showed that flashcard as a media is sufficient to improve the students' vocabulary. It is indicated through the achievement of a pretest, where only two (2) students have 500 words. However, 6 (six) students got 1200 words in the posttest.